Response of new varieties of winter wheat (Triticum aestivum L.) to the impact of environmental factors under the conditions of the Southern Forest-Steppe zone of Ukraine - М. М. Гаврилюк; П. Є. Каленич (Plant Varieties Studying and Protection)
Purpose. To define the level of impact of such factors as rate, time and methods of sowing on seed productivity and certified seeds, and the individual response of winter wheat varieties to these factors if used the ecological system of seed farming, that would allow to form and obtain genetically determined potential of variety productivity.